Influence of abiotic factors on the chemical composition of copaiba oil (Copaifera multijuga hayne): Soil composition, seasonality and diameter at breast height - Barbosa, Paula Cristina Souza; Medeiros, Raquel da Silva; Sampaio, Paulo de Tarso Barbosa; Vieira, B. Gil; Wiedemann, Larissa Silveira Moreira; Veiga-Junior, Valdir F. (Journal of the Brazilian Chemical Society, 2012)
Copaiba oils are important medicinal products used primarily for their healing and anti-inflammatory activities. Consisting of sesquiterpenes and diterpenes, these oils have variable composition which, according to the literature, may originate from several factors. In order to analyze the relationship between chemical composition and abiotic factors such as seasonality, diameter at breast height (DBH) and soil composition, sixteen of oilresin samples of Copaifera multijuga Hayne, from the Ducke Forest Reserve (Manaus City, Amazon State, Brazil), were analyzed by gas chromatography with flame ionization detection (GC-FID) and coupled with mass spectrometry (GC-MS). Thirty-five compounds were identified and the results evaluated by multivariate analysis (hierarchical cluster analysis (HCA) and principal component analysis (PCA)), allowing differentiation of the samples into two groups with different compositions. One of them presented β-caryophyllene as the major constituent, while the other presented caryophyllene oxide. This variation in composition appears to depend on soil type. Other factors previously described as essential for defining the chemical composition of copaiba oils, such as seasonality and DBH, showed no significant influence on the chemical composition of oils of this species. © 2012 Sociedade Brasileira de Quimica.